Resignifications of Identity in the Chiloé Archipelago. Speeches and Imaginaries about Mayo Chilote - Robledo Vallejos, Pablo Andrés; Peña Barriga, Gonzalo (Universidad del Rosario, 2020)
The present article interrogates the discourses of identities in resistance to the industrialization process in the Chiloé archipelago, focusing on the valuations of the social mobilizations of Mayo Chilote. Through a qualitative and exploratory research methodology, a content analysis was performed, in which the discursive particularities were identified to generate an analysis that characterized the discourses in a deep and comprehensive manner. The valuations of the social movement are analyzed considering it as the image of a discursive grammar from active subjects of said movement and the projection potential of those resistance identities as a possible local society project. The article concludes that, there are clear tensions in local identities, focusing the results on the particularities of the identities of resistance that limit their possibilities ofprojection due to a self-recognition that has not yet been consolidated.